2000
DOI: 10.1029/2000wr900109
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic behavior and random‐walk particle tracking of kinetically sorbing solutes

Abstract: Abstract. Analytical expressions are derived for the zeroth, first, and second spatial moments of sorbing solutes that follow a linear reversible kinetic mass transfer model. We determine phase-transition probabilities and closed-form expressions for the spatial moments of a plume in both the sorbed and aqueous phases resulting from an arbitrary initial distribution of solute between the phases. This allows for the evaluation of the effective velocity and dispersion coefficient for a homogeneous domain without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 25 publications
2
86
0
Order By: Relevance
“…The method extends the concept of transition probabilities [e.g., Michalak and Kitanidis, 2000;Salamon et al, 2006aSalamon et al, , 2006b] to first-order reaction networks and develops analytical solutions of the transition matrices associated with serial reactions.…”
Section: Michalak and Kitanidismentioning
confidence: 99%
See 1 more Smart Citation
“…The method extends the concept of transition probabilities [e.g., Michalak and Kitanidis, 2000;Salamon et al, 2006aSalamon et al, , 2006b] to first-order reaction networks and develops analytical solutions of the transition matrices associated with serial reactions.…”
Section: Michalak and Kitanidismentioning
confidence: 99%
“…Some of them are based on transition probabilities [Kinzelbach, 1987;Andričević and Foufoula-Georgiou, 1991;Michalak and Kitanidis, 2000] and others on the probability distribution of the particle residence time in the liquid and solid phase [Valocchi and Quinodoz, 1989;Painter et al, 2008]. In general, the efficiency of these methods depends on the parameters adopted to simulate transport.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Da can be considered an important non-dimensional number within the dual lens approach. Michalak and Kitanidis (2000) used Da to characterise the appearance of chemical sorption peaks in simulation experiments. Wehrer and Totsche (2003) used Da to characterise when breakthrough of contaminants took place under nonequilibrium conditions, Ocampo et al (2006) explored the removal of nitrate by riparian zones and demonstrated that 50 % nitrate removal occurred when Da < 1 and increased to nearly 100 % at Da = 2-20.…”
Section: Introductionmentioning
confidence: 99%
“…In subsurface hydrology, this concept has been used in the past to simulate solute transport with sorption/desorption processes (Valocchi and Quinodoz , 1989;Michalak and Kitanidis, 2000), rate-limited mass transfer processes , and kinetic network reactions (Henri and Fernàndez-Garcia, 2014). Following Michalak and Kitanidis (2000) and Henri and Fernàndez-Garcia (2014), transition probabilities can be determined from the evolution of the zeroth spatial moments of the solute plume. This is the procedure employed here.…”
Section: Development Of Transition Probabilitiesmentioning
confidence: 99%
“…In this context, Particle Tracking Methods (PTMs) constitute an efficient numerical alternative to simulate reactive transport (Kitanidis, 1994;Henri and Fernàndez-Garcia, 2014). Even though a large variety of methods exist to simulate rate-limited mass transfer processes with particle tracking (Benson and Meerschaert, 2009;Delay and Bodin, 2001;Dentz and Berkowitz , 2003;Tsang and Tsang, 2001), this method is still limited in the type of chemical reactions available, which include sorption (Tompson, 1993;Valocchi and Quinodoz , 1989;Michalak and Kitanidis, 2000), radioactive decay (Wen and Gómez-Hernández , 1996;Painter et al, 2007), first-order network reactions (Burnell et al, 2014;Henri and Fernàndez-Garcia, 2014), and simple bimolecular reactions (Benson and Meerschaert, 2008;Ding et al, 2013;Edery et al, 2009Edery et al, , 2010Paster et al, 2014) among others. None of the methods available nowadays supports multi-porosity systems with network reactions in three-dimensional randomly heterogeneous porous media.…”
Section: Introductionmentioning
confidence: 99%